Effect of contaminant on shear strength properties of soil of a landfill site / Mohamad Rosdi Daud - Daud, Mohamad Rosdi (1996)
Landfill sites have been used for many years for the disposal of industrial and domestic wastes. It is anticipated that sanitary landfill would be the most cost effective means for disposing solid wastes. Landfill site located at Bt. 10, Jalan Bukit Kemuning, Kelang which cover 12 acres of the area was selected for this purpose of study because the site was expected to be completely closed in June, 1996. An experimental-based project was conducted on samples of contaminated soils to investigate the effect of the leachate on the shear strength properties of the underlying soil of the landfill site. Soil samples were taken from site and were tested in soil laboratory. The types of test conducted were Particle size analysis, Oedometer Consolidation test, Triaxial Compression test, Atterberg Limit test.From test results, most of the soil was predominantly sand with no fraction of clay. The soil strength parameters showed that the value of cohesion was 20 kPa on average and the fractional angle was 25 degrees for soil affected by leachate and 5 degrees for original soil. It seems that the soil shear strength was more affected by the angle of internal friction than the cohesion of the soil. Soil particles affected by leachate were generally more stable as these can contribute to the chemical bonding of the aggregates. The degree of soil erodibilhy of the area was medium and this is justified by the exdstance of rill erosion.